2021
DOI: 10.3389/fphar.2021.730637
|View full text |Cite
|
Sign up to set email alerts
|

CYP450 Genotype—Phenotype Concordance Using the Geneva Micrococktail in a Clinical Setting

Abstract: Pharmacokinetic variability is a major source of differences in drug response and can be due to genetic variants and/or drug-drug interactions. Cytochromes P450 are among the most studied enzymes from a pharmacokinetic point of view. Their activity can be measured by phenotyping, and/or predicted by genotyping. Depending on the presence of drugs and/or diseases that can affect their in vivo activity, both approaches can be complementary. In 2014, the Geneva cocktail using dried blood spots was validated in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
4
20
1
Order By: Relevance
“…The present work investigated the association between CYP1A2 genetic polymorphisms and CYP1A2-selective phenacetin O-dealkylation activity or CYP1A2 mRNA expression in human liver tissues and in psychiatric patients belonging to Caucasian populations. A high inter-individual variability in the CYP1A2 activity and expression was observed in the liver tissue donors, which was consistent with the results obtained from human liver samples in a recent study by Liu et al [31] and with the CYP1A2 phenotype prediction in patients by Lorenzini et al [51]. The frequencies of the liver tissue donors with poor, intermediate and normal CYP1A2 activities were more or less similar to the frequency distribution of poor, normal and ultra-rapid metabolizer phenotypes in patients reported by Lorenzini et al [51].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present work investigated the association between CYP1A2 genetic polymorphisms and CYP1A2-selective phenacetin O-dealkylation activity or CYP1A2 mRNA expression in human liver tissues and in psychiatric patients belonging to Caucasian populations. A high inter-individual variability in the CYP1A2 activity and expression was observed in the liver tissue donors, which was consistent with the results obtained from human liver samples in a recent study by Liu et al [31] and with the CYP1A2 phenotype prediction in patients by Lorenzini et al [51]. The frequencies of the liver tissue donors with poor, intermediate and normal CYP1A2 activities were more or less similar to the frequency distribution of poor, normal and ultra-rapid metabolizer phenotypes in patients reported by Lorenzini et al [51].…”
Section: Discussionsupporting
confidence: 90%
“…A high inter-individual variability in the CYP1A2 activity and expression was observed in the liver tissue donors, which was consistent with the results obtained from human liver samples in a recent study by Liu et al [31] and with the CYP1A2 phenotype prediction in patients by Lorenzini et al [51]. The frequencies of the liver tissue donors with poor, intermediate and normal CYP1A2 activities were more or less similar to the frequency distribution of poor, normal and ultra-rapid metabolizer phenotypes in patients reported by Lorenzini et al [51]. In a previous study [52], a strong correlation was reported between hepatic CYP1A2 activity and mRNA expression, which was confirmed by our findings in the liver tissue donors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study is a paediatric subpart of three previously published studies that included children and adults (Lloret-Linares et al, 2017;Rollason et al, 2020a;Ing Lorenzini et al, 2021). The studies were approved by the Ethics Commission of the Canton of Geneva, Geneva (Switzerland) (study numbers: 15-225, 15-080 and 14-244) (Lloret-Linares et al, 2017;Rollason et al, 2020a;Ing Lorenzini et al, 2021).…”
Section: Patients and Settingmentioning
confidence: 99%
“…The present work indicated that CYP2B6 genetic polymorphisms influenced the expression and activity of CYP2B6 enzyme to some extent; however, the significance of phenoconverting non-genetic factors in enzyme function was comparable with that of genetic factors or even phenoconversion masked the effect of CYP2B6 allelic variants. Ing Lorenzini et al evaluated the predictive values of CYP genotypes on CYP-mediated drug metabolism in patients, and observed relatively good CYP2B6 genotype–phenotype concordance for poor and rapid metabolizers (67% and 100%), but more variable for intermediate and normal metabolizers (0% and 38%) 89 . It should be noted that the number of patients involved in the interpretation of CYP2B6 genotype–phenotype concordance was limited (N = 36).…”
Section: Discussionmentioning
confidence: 99%